Luminatorul: The Identity, confessional and national Message - GROSSU, Silvia (Études Interdisciplinaires en Sciences humaines, 2020)
Abstract: In this study, paying homage to the clerical magazine Luminătorul (The Enlightener) 110 years after its first issue, we propose a segment of the national awakening movement of the Bessarabians, focused on the hard work of identity legitimation on two essential levels – confessional and national.